Genetic differentiation in Khaya Ivorensis A. Chev., a threaten tree of evergreen African rainforests - Gaël U. D. Bouka; Charles Doumenge; Marius R. M. Ekué; Jérôme Duminil; Jacques Florence; Bernd Degen; Jean Joël Loumeto; Doyle McKey; Olivier J. Hardy (Tree Genetics & Genomes, 2024)

Phylogenetic positions of Thai members of Gymnema, Gymnemopsis and Sarcolobus (Apocynaceae, Asclepiadoideae, Marsdenieae), and two new Sarcolobus species uncovered by morpho-molecular evidence - Manit Kidyoo; Aroonrat Kidyoo; Doyle McKey (Journal of Plant Research, 2024)

Molecular phylogeny of Vincetoxicum (Apocynaceae, Asclepiadoideae) from Thailand and integrative taxonomy corroborating a new cryptic species within Vincetoxicum kerrii - Aroonrat Kidyoo; Manit Kidyoo; Doyle McKey; Rumsaïs Blatrix (Journal of Plant Research, 2024)

Socio-Ecological Approach to a Forest-Swamp-Savannah Mosaic Landscape Using Remote Sensing and Local Knowledge: a Case Study in the Bas-Ogooué Ramsar Site, Gabon - Christophe Demichelis; Johan Oszwald; Doyle Mckey; Paul-Yannick Bitome Essono; Guy-Philippe Sounguet; Jean-Jacques Braun (Environmental Management, 2023)

High outcrossing rates in a self‐compatible and highly aggregated host‐generalist mistletoe - Manru Li; Yi Sui; Xuanni Wang; Zhanxia Ma; Yahuang Luo; Sasith Tharanga Aluthwattha; Doyle McKey; Benoit Pujol; Jin Chen; Ling Zhang (Molecular Ecology, 2022)
Plants have evolved various strategies to avoid inbreeding, but the mass flowering displayed by many plants predisposes them to within‐plant pollen movements and self‐pollination. Mistletoes often aggregate at multiple spatial scales. Their bird pollinators often visit several flowers of the same individual and of others on the same host tree. We hypothesized that hermaphroditic mistletoes have self‐incompatibility mechanisms that reduce or prevent selfing. Whether their spatial distribution, affected by host specificity, host distribution, and the behaviour of seed dispersers, influences their mating system and population genetic structure remains unclear. We studied how mating system and spatial distribution affect genetic structure in four populations of the host‐generalist mistletoe Dendrophthoe pentandra in southwestern China using microsatellite markers and progeny arrays. We also characterized the fine‐scale spatial genetic structure among 166 mistletoes from four host trees in one population. Prevalence and intensity of infection both appeared to vary among host species, strongly affecting the degree of aggregation. Host tree size had a strong effect on infection intensity. Surprisingly, manual pollination experiments indicated that D. pentandra is self‐compatible, but genetic analyses revealed that outcrossing rates were higher than expected in all four populations (MLTR t m 0.83–1.20, Bayesian t m 0.772–0.952). Spatial genetic structure was associated with distance between host trees but not at shorter scales (within hosts). Our results demonstrate that the combination of bird pollination, bird‐mediated seed dispersal, and post‐dispersal processes result in outcrossing and maintain relatively high diversity in the presence of biparental inbreeding, despite very high local densities and possible self‐compatibility.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Molecular phylogenetic analysis and taxonomic reconsideration of Ceropegia hirsuta (Apocynaceae, Asclepiadoideae) reveal a novelty in Thailand, Ceropegia citrina sp. nov., with notes on its pollination ecology - Aroonrat Kidyoo; Manit Kidyoo; Rumsaïs Blatrix; Gwenaëlle Deconninck; Doyle McKey; Paweena Ekkaphan; Magali Proffit (Plant Systematics and Evolution, 2021)

The symbiosis between Philidris ants and the ant-plant Dischidia major includes fungal and algal associates - Rumsaïs Blatrix; Aroonrat Kidyoo; Manit Kidyoo; Jittra Piapukiew; Anchittha Satjarak; Chanita Paliyavuth; Wachana Boonchai; Doyle McKey (Symbiosis, 2021)

Genetic diversity and differentiation among the species of African mahogany (Khaya spp.) based on a large SNP array - Birte Pakull; Marius R. M. Ekué; Ulrich G. Bouka Dipelet; Charles Doumenge; Doyle B. McKey; Jean Joël Loumeto; Emmanuel Opuni-Frimpong; Soulemane N. Yorou; Blandine M. Y. Nacoulma; Kudzo A. Guelly; Lolona Ramamonjisoa; Darren Thomas; et al. (Conservation Genetics, 2019)

Comparative analysis of spatial genetic structure in an ant–plant symbiosis reveals a tension zone and highlights speciation processes in tropical Africa - Rumsaïs Blatrix; Jean Peccoud; Céline Born; Finn Piatscheck; Laure Benoit; Mathieu Sauve; Champlain Djiéto‐Lordon; Christiane Atteke; Jan J. Wieringa; David J. Harris; Doyle McKey (Journal of Biogeography, 2017)
Aim Pleistocene climatic oscillations induced range fluctuations in African rain forest organisms and may have shaped species diversification through allopatric speciation events. We compared the spatial genetic structure of two forest species that live in obligate symbiosis and thus must have experienced the same range fluctuations, as a means to discriminate incipient speciation from transient differentiation simply resulting from past divergence. Location Western central Africa. Methods We genotyped 765 individuals of the tree Barteria fistulosa and 605 colonies of its symbiotic ant Tetraponera aethiops at 12 and 13 microsatellite loci, respectively. We compared the spatial genetic structure of the two symbionts by using Bayesian clustering algorithms, isolation‐by‐distance analyses and clines of synthetic alleles. We used species niche modelling (climatic and soil variables) to investigate ecological variables associated with genetic discontinuities in tree populations. Results The trees and the ants showed congruent patterns of spatial genetic structure. However, the trees showed a very steep genetic discontinuity between groups north and south of latitude 1° N, which was much weaker in the ants. There was no evidence for effective gene flow between the two tree lineages in contact at the transition zone, despite the presence of a few hybrids. Niche modelling did not predict the occurrence of northern trees south of this genetic transition, and vice versa. Main conclusions The genetic discontinuity near latitude 1° N is inferred to be a tension zone resulting from reproductive incompatibilities between previously allopatric tree lineages. This tension zone may have stabilized at a climatic transition (between boreal and austral seasonal regimes), and matches patterns of genetic structure previously observed in other forest plant species. Our results illustrate independent speciation between two species that live in specific and obligate symbiosis and suggest that a tension zone may separate lineages of several central African forest plants near the thermal equator.

Perceptual selection and the unconscious selection of ‘volunteer’ seedlings in clonally propagated crops: an example with African cassava (Manihot esculenta Crantz) using ethnobotany and population genetics - Marc Delêtre; Trevor R. Hodkinson; Doyle McKey (Genetic Resources and Crop Evolution, 2017)

Origin of mound-field landscapes: a multi-proxy approach combining contemporary vegetation, carbon stable isotopes and phytoliths - Delphine Renard; Jago Jonathan Birk; Bruno Glaser; José Iriarte; Gilles Grisard; Johannes Karl; Doyle McKey (Plant and Soil, 2012)

Tree diversity and conservation value of Ngovayang’s lowland forests, Cameroon - Christelle F. Gonmadje; Charles Doumenge; Doyle McKey; Gildas P. M. Tchouto; Terry C. H. Sunderland; Michael P. B. Balinga; Bonaventure Sonké (Biodiversity and Conservation, 2011)

The Evolution of Communication in Two Ant-Plant Mutualisms - Marion Vittecoq; Champlain Djieto-Lordon; Bruno Buatois; Laurent Dormont; Doyle McKey; Rumsaïs Blatrix (Evolutionary Biology, 2011)

Population genetics of Manihot esculenta ssp. flabellifolia gives insight into past distribution of xeric vegetation in a postulated forest refugium area in northern Amazonia - ANNE DUPUTIÉ; MARC DELÊTRE; JEAN‐JACQUES DE GRANVILLE; DOYLE MCKEY (Molecular Ecology, 2009)
The Guianas have often been proposed as a forest refugium; however, this view has received little testing. Studies of population genetics of forest taxa suggest that the central part of French Guiana remained forested, while the southern part (currently forested) may have harboured more open vegetation. Insights into the population structure of species restricted to non‐forested habitats can help test this hypothesis. Using six microsatellite loci, we investigated the population genetics of French Guianan accessions of Manihot esculenta ssp. flabellifolia , a taxon restricted to coastal savannas and to rocky outcrops in the densely forested inland. Coastal populations were highly differentiated from one another, and our data suggest a recent colonization of these savannas by M. esculenta ssp. flabellifolia in a west‐to‐east process. Coastal populations were strongly differentiated from inselberg populations, consistent with an ancient separation of these two groups, with no or low subsequent gene flow. This supports the hypothesis that the central part of the region may have remained forested since the Last Glacial Maximum, impeding the establishment of Manihot . Contrary to coastal populations, inselberg Manihot populations were strikingly homogeneous at a broad spatial scale. This suggests they were connected until recently, either by a large continuous savanna area or by smaller, temporary disturbed areas shifting in space.

Natural hybridization between a clonally propagated crop, cassava ( Manihot esculenta Crantz) and a wild relative in French Guiana - ANNE DUPUTIÉ; PATRICE DAVID; CHANTAL DEBAIN; DOYLE MCKEY (Molecular Ecology, 2007)
Because domestication rarely leads to speciation, domesticated populations often hybridize with wild relatives when they occur in close proximity. Little work has focused on this question in clonally propagated crops. If selection on the capacity for sexual reproduction has been relaxed, these crops would not be expected to hybridize with their wild relatives as frequently as seed‐propagated crops. Cassava is one of the most important clonally propagated plants in tropical agriculture. Gene flow between cassava and wild relatives has often been postulated, but never demonstrated in nature. We studied a population of a wild Manihot sp. in French Guiana, which was recently in contact with domesticated cassava, and characterized phenotypes (10 morphological traits) and genotypes (six microsatellite loci) of individuals in a transect parallel to the direction of hypothesized gene flow. Wild and domesticated populations were strongly differentiated at microsatellite loci. We identified many hybrids forming a continuum between these two populations, and phenotypic variation was strongly correlated with the degree of hybridization as determined by molecular markers. Analysis of linkage disequilibrium and of the diversity of hybrid pedigrees showed that hybridization has gone on for at least three generations and that no strong barrier prevents admixture of the populations. Hybrids were more heterozygous than either wild or domesticated individuals, and phenotypic comparisons suggested heterosis in vegetative traits. Our results also suggest that this situation is not uncommon, at least in French Guiana, and demonstrate the need for integrated management of wild and domesticated populations even in clonally propagated crops.

Propagule Quantity and Quality in Traditional Makushi Farming of Cassava (Manihot esculenta): A Case Study for Understanding Domestication and Evolution of Vegetatively Propagated Crops - Marianne Elias; Hélène Lenoir; Doyle McKey (Genetic Resources and Crop Evolution, 2007)

Local genetic diversity of sorghum in a village in northern Cameroon: structure and dynamics of landraces - Adeline Barnaud; Monique Deu; Eric Garine; Doyle McKey; Hélène I. Joly (Theoretical and Applied Genetics, 2006)

Ancient and recent evolutionary history of the bruchid beetle, Acanthoscelides obtectus Say, a cosmopolitan pest of beans - NADIR ALVAREZ; DOYLE MCKEY; MARTINE HOSSAERT‐MCKEY; CÉLINE BORN; LÉNY MERCIER; BETTY BENREY (Molecular Ecology, 2005)
Acanthoscelides obtectus Say is a bruchid species of Neotropical origin, and is specialized on beans of the Phaseolus vulgaris L. group. Since the domestication and diffusion of beans, A. obtectus has become cosmopolitan through human‐mediated migrations and is now a major pest in bean granaries. Using phylogeographic methods applied to mitochondrial DNA (mtDNA) and nuclear microsatellite molecular markers, we show that the origin of this species is probably further south than Mesoamerica, as commonly thought. Our results also indicate that A. obtectus and its Mesoamerican sister species Acanthoscelides obvelatus , two morphologically close species differing principally in voltinism, speciated in allopatry: A. obtectus (multivoltine) arising in Andean America and A. obvelatus (univoltine) in Mesoamerica. In contrast to Mesoamerica where beans fruit once yearly, wild beans in Andean America fruit year‐round, especially in regions showing little or no seasonality. In such habitats where resources are continuously present, multivoltinism is adaptive. According to existing hypotheses, multivoltinism in A. obtectus is a new adaptation that evolved after bean domestication. Our data suggest the alternative hypothesis that multivoltinism is an older trait, adapted to exploit the year‐round fruiting of wild beans in relatively aseasonal habitats, and allowed A. obtectus to become a pest in bean granaries. This trait also permitted this species to disperse through human‐mediated migrations associated with diffusion of domesticated beans. We also show that diversity of Old World A. obtectus populations can be quite well explained by a single colonization event about 500 bp . Human‐mediated migrations appear not to be rare, as our results indicate a second more recent migration event from Andean America to Mexico.

Microevolution in agricultural environments: how a traditional Amerindian farming practice favours heterozygosity in cassava ( Manihot esculenta Crantz, Euphorbiaceae) - Benoît Pujol; Patrice David; Doyle McKey (Ecology Letters, 2005)
We demonstrate a novel case of selection for heterozygosity in nature, involving inadvertent human selection on a population of domesticated plants. Amerindian farmers propagate cassava ( Manihot esculenta ) clonally by cuttings. Seedlings also appear spontaneously in fields, and farmers allow them to grow, later using some for cuttings. These ‘volunteers’ contribute new genotypes. However, many are inbred, whereas multiplied clones are highly heterozygous. We demonstrate the selective retention of heterozygous volunteers. When farmers weeded fields, they killed small volunteers, but retained large ones. Plant size and heterozygosity were correlated, and both increased after weeding. The process we document allows maintenance of genotypically diverse and heterozygous clonal stocks. Demonstrating heterosis in nature usually requires large sample sizes, but novel features of our system allowed escape of this constraint. Traditional agroecosystems offer unusual opportunities for the microevolutionary studies required to give on‐farm conservation of genetic resources a solid scientific basis.

Colony structure in a plant-ant: behavioural, chemical and genetic study of polydomy in Cataulacus mckeyi (Myrmicinae) - Gabriel Debout; Erick Provost; Marielle Renucci; Alain Tirard; Bertrand Schatz; Doyle McKey (Oecologia, 2003)

Extraction and quantification of "condensed tannins" as a measure of plant anti-herbivore defence? Revisiting an old problem - Martin Heil; Birgit Baumann; Claude Andary; Eduard K. Linsenmair; Doyle McKey (The Science of Nature, 2002)

How identity of the homopteran trophobiont affects sex allocation in a symbiotic plant-ant: the proximate role of food - Laurence Gaume; Doyle McKey (Behavioral Ecology and Sociobiology, 2002)

Variation in the effectiveness of biotic defence: the case of an opportunistic ant-plant protection mutualism - Bruno Giusto; Marie-Charlotte Anstett; Edmond Dounias; Doyle B. McKey (Oecologia, 2001)

Traditional management of cassava morphological and genetic diversity by the Makushi Amerindians (Guyana, South America): Perspectives for on-farm conservation of crop genetic resources - Marianne Elias; Doyle McKey; Olivier Panaud; Marie Charlotte Anstett; Thierry Robert (Euphytica, 2001)

Sexual specialization in two tropical dioecious figs - Aviva Patel; Doyle McKey (Oecologia, 1998)

Benefits conferred by "timid" ants: active anti-herbivore protection of the rainforest tree Leonardoxa africana by the minute ant Petalomyrmex phylax - Laurence Gaume; Doyle McKey; Marie-Charlotte Anstett (Oecologia, 1997)

Modeling the Persistence of Small Populations of Strongly Interdependent Species: Figs and Fig Wasps - Marie‐Charlotte Anstett; Martine Hossaert‐McKey; Doyle McKey (Conservation Biology, 1997)
Conservation problems are usually studied at the population or ecosystem levels. Formulating predictive theory for the domain in between has been difficult. Fig trees and their pollinating wasps, principally tropical groups of organisms, form pairs of obligate mutualists that provide unique opportunities for studying the influence of species interactions on the survival of small populations. Survival of each partner depends on that of the associated species. The pollinator population can be maintained only if figs are produced year‐round. Because fig trees flower synchronously at the individual level, wasps have to locate a new individual host tree at each generation. We describe results of simulation models estimating the minimum number of trees required to maintain a wasp population using two levels of the criteria: (1) different probability of survival (50% and 99%) and (2) different time of survival (5 or 1000 years). We also examined how these different estimates are sensitive to differences in the seasonality of flowering period and in the length of the period of female receptivity in figs. Such estimates can be used to understand the potential effects of the reduction of fig population size via fragmentation. Unlike most studies on the effect of low population size on population viability, our paper focuses on maintenance of a biotic interaction, rather than on single‐species dynamics. The biotic interaction on which we focus is important because figs in many tropical ecosystems may be keystone resources for frugivores that are in turn essential seed dispersal agents for other plants.